Chusquea giuliettiae, a new species of C. subg. Chusquea (Poaceae: Bambusoideae: Bambuseae) from the highlands of the Espinhaço Range, Brazil - Vidal, Kaio Vinicius De A.; Oliveira, Iasmin Laiane De C.; Welker, Cassiano A. Dorneles; Clark, Lynn G.; Oliveira, Reyjane P. (Phytotaxa, 2025)
Chusquea subg. Chusquea, with over 100 accepted species, is the most diverse subgenus of Chusquea. This diversity is divided into six sections and the C. meyeriana informal group, the latter currently comprising nine species endemic to eastern Brazil. Recent studies have focused on updating the taxonomy of this group to understand its diagnostic features and placement within the genus. We confirm the presence of another new species within the C. meyeriana informal group, herein described as Chusquea giuliettiae. The new species is morphologically similar to C. clemirae, C. cordata, C. longispiculata, and C. parviligulata based on its triangular central bud, culm leaf sheaths free or only slightly fused at the base, and culm leaves deciduous to late deciduous, as well as synflorescence structure. Chusquea giuliettiae is distinguished by having smaller and more foliage leaves per complement and smaller synflorescences and spikelets than these other four species. It occurs along the Espinhaço Range, from the Chapada Diamantina, in Bahia state, to the Diamantina Plateau in Minas Gerais state. After the description of C. giuliettiae, the C. meyeriana informal group will consist of 10 species, and the genus Chusquea will comprise 51 species occurring in Brazil, 47 of which are endemic.